Tourism Development: The Challenges of Achieving Sustainable Livelihoods in Bhutan's Remote Reaches. (24th September 2015) - Suntikul, Wantanee; Dorji, Ugyen
Abstract: Merak–Sakteng is a remote area of Bhutan, which is targeted for development of tourism owing to the unique culture and way of life of the semi‐nomadic local 'Brokpa' people, whose livelihoods depend on herding yaks and sheep. These livestock enter forests where local residents and government see their grazing as threatening their crops and causing environmental degradation. The semi‐nomadic life centred on livestock, which has long been essential to Brokpa culture and economy, thus comes under threat. The opening of Merak–Sakteng to tourism is intended to address this conflict by lessening the Brokpas' economic dependence on livestock. This paper reports on research into the potential of tourism to transform this ethnic minority's economic way of life through the introduction of tourism into the local livelihood mix. Sustainable livelihoods issues are investigated through a consideration of both economic and socio‐cultural aspects of the local way of life, based on observation, and the findings of a survey of local people, semi‐structured interviews with village leaders and government officials concerning development of the area. The survey found that despite land‐use conflicts and limited grazing land, Brokpas still aspired to spend money gained from tourism on purchasing more yaks, which may escalate land‐use conflicts and threaten environmental sustainability. Copyright © 2015 John Wiley & Sons, Ltd.